The Sosialisasi dan Edukasi Budidaya Jamur Tiram sebagai Upaya Pemberdayaan Masyarakat Berbasis Ketahanan Pangan di RT 20 Sumur Dewa - Marta Marulina Putri; Revinda Tirta Carryna; Irfan Ahmadi; Khoirul Anam; M. Noufal Syafiq Fauzan; Selvi Apri Nola; Yuni Nurindah; Wiji Aziz Hari Mukti (Yayasan Darussalam Bengkulu, 2026)
This community service article aims to describe and analyze the implementation of socialization and education activities on oyster mushroom (Pleurotus ostreatus) cultivation in RT 20 Sumur Dewa, Bengkulu City, as an effort to empower communities and strengthen household food security. The study employed a descriptive approach using simple mixed methods by combining qualitative and quantitative data. Qualitative data were collected through participatory observation, in-depth interviews with 15 key informants, and documentation, while quantitative data were obtained through pre-test and post-test administered to 25 participants. Qualitative data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing, whereas quantitative data were analyzed descriptively to determine changes in participants' knowledge levels. The results showed that the program was implemented through three stages, namely preparation, implementation, and evaluation accompanied by mentoring activities. The average participant score increased from 45 in the pre-test to 82 in the post-test, indicating an improvement in knowledge and understanding regarding oyster mushroom cultivation techniques. Supporting factors included strong community enthusiasm, support from local leaders, and the availability of local raw materials, while limited capital and cultivation space became the main constraints. The activity demonstrates that oyster mushroom cultivation has the potential to become a sustainable community-based home industry that contributes to food security and additional household income.